CORRELATION BETWEEN SENIORITY AND VERBAL ABUSE AMONG TEENAGE GAMERS - Suryani Madaniyah; Hetty Murdiyani; Fety Khosianah (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
This study investigates the relationship between seniority and verbal abuse among teenage gamers who play in group settings. Using a quantitative correlational approach, data were collected from 61 respondents through purposive sampling. A Likert-scale questionnaire was employed to measure both seniority and verbal abuse. The results of Pearson’s correlation analysis indicated a significance level of 0.772 (p > 0.05) with a correlation coefficient of -0.038, suggesting no significant relationship between seniority and verbal abuse among the participants. This research provides insights into the dynamics of hierarchy and communication patterns within gaming communities.